The influence of a vegan diet on body composition, performance and the menstrual cycle in young, recreationally trained women– a 12-week controlled trial - Eduard Isenmann; Isabella Trojak; Alessio Lesch; Jan Schalla; Tim Havers; Patrick Diel; Stephan Geisler (Journal of the International Society of Sports Nutrition)
Background An increasing number of people, including recreational trained individuals, choose not to consume animal products and follow a vegan diet. Young women in particular are switching to a vegan diet. Studies have shown no difference in performance and muscle adaptations between a balanced vegan and an omnivorous diet. However, there are hardly any studies on the transition phase from an omnivorous to a vegan diet and the potential difficulties. Therefore, this study aimed to investigate the influence of a vegan dietary transition and its effects on body composition, physical performance, and menstrual cycle in young, recreationally trained women.Methods Ten young healthy women (23.8 ± 2.0 years, 173.0 ± 5.8 cm) were recruited to participate in this 12-week controlled study (4-week omnivorous phase, 8-week vegan intervention). At the beginning and before the vegan phase, all participants were informed about a balanced diet for fitness-oriented individuals and a vegan lifestyle. They were supervised by a sports dietitian for the entire 12 weeks. Explicit instructions and regular checks on macronutrient distribution were not carried out but had to be implemented independently. The diet was documented using FDDB Extender. The training habits were not explicitly specified, but should not be changed over the entire period. At baseline (T0) and 4-week intervals (T1, T2, T3), body composition (body weight, skeletal muscle mass, fat mass) and performance (squat, countermovement jump) were tested. In addition, the menstrual cycle was examined every two days using saliva samples and a cycle diary.Results Between treatments, there was a significant decrease in absolute (T0: 94.44 ± 20.37 kcal; T3: 71.67 ± 27.64 kcal; p < 0.001) and in relative protein intake (T0: 1.39 ± 0.28 g/kg BW; T3: 1.06 ± 0.37 g/kg BW; p < 0.05). In carbohydrate consumption, a significant increase was observed (T0: 240.11 ± 53.15 kcal; T3: 266.89 ± 49.01 kcal; p < 0.001). During the vegan phase, a significant decrease in body weight (T0: 68.19 ± 6.47 kg, T3: 67.73 ± 6.07 kg; p < 0.001) and skeletal muscle mass (T0: 29.40 ± 2.23 kg; T3: 28.74 ± 2.55 kg; p < 0.001) was observed. No changes were noted in squat performance. The countermovement jump showed a significant decrease in the vegan phase (T0: 26.08 ± 3.44 cm; T3: 23,62 ± 1,00 p < 0.05), but also a significant time effect starting in the omnivorous phase (p < 0.001). No effects were found on hormone concentrations of individual menstrual cycles.Conclusion The dietary change resulted in a shift in overall macronutrient distribution. Relative protein intake was significantly lower during the vegan phase than during the omnivore phase. This was also observed in a slight decrease in skeletal muscle mass. No clear effects on performance and menstrual cycle were observed during the first eight weeks. The results suggest that despite the knowledge of a balanced diet and in particular the recommendations for a vegan diet, the implementation of a vegan diet in everyday life could be associated with a number of difficulties for recreationally trained women. However, it should be noted that the vegan phase was only conducted for eight weeks and no statement can be made about the long-term effects or on well-trained female athletes.